2017
DOI: 10.1080/13803395.2017.1373746
|View full text |Cite
|
Sign up to set email alerts
|

Auditory attention in autism spectrum disorder: An exploration of volumetric magnetic resonance imaging findings

Abstract: Studies have shown that individuals with autism spectrum disorder (ASD) tend to perform significantly below typically developing individuals on standardized measures of attention, even when controlling for IQ. The current study sought to examine within ASD whether anatomical correlates of attention performance differed between those with average to above-average IQ (AIQ group) and those with low-average to borderline ability (LIQ group) as well as in comparison to typically developing controls (TDC). Using aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 136 publications
(156 reference statements)
4
2
0
Order By: Relevance
“…No statistically significant alterations were detected between ASD‐no‐ID and no‐ID controls. This result is in line with a recent study in which larger volumes in the ASD group were related to poorer performance (Lalani et al, ). Further, this finding is interesting in that recent investigations suggested a participation of the brainstem in cognitive processes (D'Aes et al, ; Fu et al, ), and points at the relevance of further investigating the relationship between brainstem volume and intellectual functioning in children with ASD.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…No statistically significant alterations were detected between ASD‐no‐ID and no‐ID controls. This result is in line with a recent study in which larger volumes in the ASD group were related to poorer performance (Lalani et al, ). Further, this finding is interesting in that recent investigations suggested a participation of the brainstem in cognitive processes (D'Aes et al, ; Fu et al, ), and points at the relevance of further investigating the relationship between brainstem volume and intellectual functioning in children with ASD.…”
Section: Discussionsupporting
confidence: 93%
“…No statistically significant alterations were detected between ASD-no-ID and no-ID controls. This result is in line with a recent study in which larger volumes in the ASD group were related to poorer performance (Lalani et al, 2018).…”
Section: Shape Analysissupporting
confidence: 93%
See 1 more Smart Citation
“…The literature reports common difficulties in children with ASD in tasks where inhibitory control, auditory sustained attention, and short-term verbal memory are involved (e. g. Corbett & Constantine, 2006;Geurts et al, 2014;Lalani et al, 2018). In fact, in the present study we used a group of children with typical development as a comparison group.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the executive functions, children with ASD have also shown deficits in other higher-order cognitive processes that are not exclusively executive in nature, such as verbal fluency (e. g. Begeer et al, 2014;Pastor-Cerezuela, Fernández-Andrés, Feo-Álvarez & González-Sala, 2016), sustained attention (visual: e. g. Chien et al, 2014;and auditory: Corbett & Constantine, 2006), and short-term memory (visual: e. g. Chien et al, 2015;Jaworski & Eigsti, 2017; and auditory / verbal: e. g. Lalani et al, 2018). Some studies carried out with samples with no clinical diagnosis have found a link between sensory and cognitive processing (e. g. Humes, Busey, Craig, & Kewley-Port, 2013, carried out with adults) and between sensory processing and executive functioning (Adams, Feldman, Huffman, & Loe, 2015, carried out with preterm preschoolers).…”
Section: Sensory Executive and Cognitive Dysfunctions In Asdmentioning
confidence: 99%